Comprehensive Analysis of lncRNAs, miRNAs and mRNAs in Mouse Hippocampus With Hepatic Encephalopathy - Zhang, Huijie; Zhang, Wenjun; Yu, Guangyin; Li, Fang; Hui, Yuqing; Cha, Shuhan; Chen, Meiying; Zhu, Wei; Zhang, Jifeng; Guo, Guoqing; Gong, Xiaobing (Frontiers in Genetics, 2022)
Hepatic encephalopathy (HE) often presents with varying degrees of cognitive impairment. However, the molecular mechanism of its cognitive impairment has not been fully elucidated. Whole transcriptome analysis of hippocampus between normal and HE mice was performed by using RNA sequencing. 229 lncRNAs, 49 miRNAs and 363 mRNAs were differentially expressed in HE mice. The lncRNA-miRNA-mRNA interaction networks were established, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed. Dysregulated RNAs in interaction networks were mainly involved in synaptic plasticity and the regulation of learning and memory. In NH4Cl-treated hippocampal neurons, the dendritic spine density and maturity decreased significantly, the amplitude and frequency of mIPSC increased, while the amplitude and frequency of mEPSC decreased. These manifestations can be reversed by silencing SIX3OS1. Further research on these no-coding RNAs may lead to new therapies for the treatment and management of brain dysfunction caused by HE.